جزئی مقاصد شریعت کاایک تعارفی جائزہ: Partial Objectives An introductory review of Shariah - Tahir, Muhammad; Qazi , Dr. Shabana (Journal of Quranic and Social Studies, 2022)
The gist of this article is that the purposes of Shari’ah have many meanings. Here it refers to the benefits and advantages of partial rulings which contain the precepts of the rule. ۔ Acquisition of religious and worldly benefits and spices. ۔ The issue of religious and secular losses and riots is a separate issue. If there is a clash between religious and secular interests, then which benefit will be abandoned and which benefit will be preferred? Although the principle and general rule is that religious interests will be preferred.This knowledge has been described by Shah Waliullah as the summary and flower of all sciences and knowledge of this knowledge is a sign of man’s wisdom and prudence. Therefore, expediency, wisdom, profit, and mysteries and rules, etc., which are found in religious sciences, the same topics have become a permanent subject and have taken the form of a permanent knowledge. That the benefit and fruit of this knowledge is religion, success in this world and in the hereafter, and protection from all kinds of harms and gain